Student Learning Outcomes using the Snow Cube Throwing Learning Model with Cooperative Settings - Nenden Mutiara Sari; Hanhan Subhan Munawar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
The purpose of this study was to analyze the differences in learning outcomes between students who received snow cube throwing and students who received an expository learning model. In addition to these objectives, another objective of this study is to test the effectiveness of using the snow cube throwing learning model on student learning outcomes. The research method used was a quasi-experimental with a non equivalent control group design. The population of this study were all students of class XI at SMAN 5 Cimahi. The sample in this study consisted of 2 groups, namely the experimental class and the control class selected by purposive sampling. Each group consisted of 40 students, so that there were 80 students who were sampled in this study. Data analysis in this study used the independent sample t-test and effect size. The results of the data analysis show that the learning outcomes of students who get the snow cube throwing model are better than the learning outcomes of students who get the expository model. The effectiveness of using the snow cube throwing model is more effective in improving student learning outcomes, as indicated by the value of the effect size which is included in the high category.